Several Shoot Of Cassava Plants - Ananto, Ananto (Agrium, 2019)
Research on Various Connections of Manihot esculenta crant for thepurpose of obtaining good quality cassava seeds and increasing farmers' income,especially cassava farmers. This study was compiled based on a completerandomized design (CRD) with four treatment levels and three replications ofeach replication consisting of four treatments, consisting of control (A),connecting local cinnamon yams with yellow cassava (B), connecting localcinnamon yams with plain cassava (C), connecting local sweet potatoes withelephant cassava (D). The variables observed were weight of fresh tuber weight(kg), number of tubers (fruit), longest tuber length (cm). Splicing using localcassava rootstock with elephant cassava stem (D), gives a better influence onfresh tuber weight (6.89 kg), tuber number (20.67 pieces) and longest tuber length (63.55 cm).Key words: Cassava, shoots, Varieties